Omental Torsion after Laparoscopic Roux-en-Y Gastric Bypass Mimicking Appendicitis: A Case Report and Review of the Literature - Alexandre Descloux; Giacinto Basilicata; Antonio Nocito (Case Reports in Surgery)
Introduction. Laparoscopic Roux-en-Y gastric bypass (LRYGBP) is a common procedure in obesity surgery. The aim of an antecolic approach is to reduce the rate of internal herniation. Our aim is to make bariatric surgeons aware of another possible complication of antecolic LRYGBP. Methods and Results. We present a case report of omental torsion 24 months after antecolic LRYGBP presenting as an acute abdomen, suggesting appendicitis. During diagnostic laparoscopy, omental infarction due to torsion was observed. Resection of the avital omentum was performed. Discussion. Omental torsion after antecolic LRYGBP is a rare complication. When appearing in the early postoperative phase, it may mimic an anastomotic leakage. It may also occur as late complication, presenting with acute abdomen as an appendicitis.